Impairment of ADP-Induced Platelet Aggregation by Hashish Components - Levy, Rachel; Schurr, Avital; Nathan, Ilana; Dvilanski, Alexander; Livne, Avinoam (Thrombosis and Haemostasis, 1976)
ADP-induced aggregation of washed human platelets is inhibited by the hashish components Δ1-tetrahydrocannabinol (THC) and cannabidiol (CBD). The inhibition is counteracted by added ADP. When the cannabinoids are present at concentrations higher than 10−5M, the platelets aggregate non-reversibly, independently of an added inducer, apparently due to lysis and release of endogenous inducers. THC is clearly more potent than CBD in exhibiting the biphasic effect. Collagen- and thrombin-induced aggregation of washed platelets are hardly affected by the cannabinoids. THC and CBD also curtail ADP-induced reversible aggregation in platelet-rich plasma, while serotonin release and irreversible aggregation, caused by either ADP, collagen or thrombin, are not affected by the cannabinoids in platelet-rich plasma. The data point to associated sites for ADP and the cannabinoids on the platelet membrane.